Estimating the return to schooling using the Mincer equation - Harry Anthony Patrinos (IZA World of Labor, 2016)
The Mincer equation—arguably the most widely used in empirical work—can be used to explain a host of economic, and even non-economic, phenomena. One such application involves explaining (and estimating) employment earnings as a function of schooling and labor market experience. The Mincer equation provides estimates of the average monetary returns of one additional year of education. This information is important for policymakers who must decide on education spending, prioritization of schooling levels, and education financing programs such as student loans.
Keywords: J13; J16; J21; J22; P23; P52; 330; human capital; labor market experience; earnings; income distribution; Jacob Mincer